Coelomic Fluid Evaluation in Clinically Normal Ochre Sea Stars Pisaster ochraceus: Cell Counts, Cytology, and Biochemistry Reference Intervals. Issue 3 (6th June 2019) - Wahltinez, Sarah J.; Stacy, Nicole I.; Lahner, Lesanna L.; Newton, Alisa L.
Abstract: Coelomic fluid sampling is a noninvasive technique that is used to access the body fluid of sea stars for diagnostics and research. Given recent mortality events including sea star wasting disease, which has killed millions of sea stars along the Pacific coast since 2013, there is a need for validated diagnostic tests to evaluate sea star health. The objectives of this study were to establish coelomic fluid reference intervals for clinically normal ochre sea stars Pisaster ochraceus in an open system aquarium, to describe the cytologic findings, and to compare the chemistries of coelomic fluid with open system tank water. Coelomic fluid from 26 clinically normal sea stars was sampled for coelomocyte counts, cytologic evaluation, and biochemical analysis including magnesium, sodium, potassium, chloride, calcium, and total protein. The number of coelomocytes and total protein did not fit normal distribution and were excluded from analyses. Reference intervals were established for other chemistry analytes. There was no statistical difference in biochemistries between sea star coelomic fluid and water from five open system tanks, which supports previous evidence that sea stars are osmoconformers. Very low numbers of coelomocytes were observed cytologically. These results provide a useful baseline and diagnostic tool for health assessments of sea stars.